A PSYCHOLOGICAL ANALYSIS OF THE MAIN CHARACTER IN MARSIRAJI THAHIR’S KABAR BUNGA - Afifulloh, M (Lire Journal (Journal of Linguistics and Literature), 2019)
This paper aims to describe the female characters of the novel, her conflicts and its causes, and the impact of the conflicts experienced by the main character in the novel Kabar Bunga by Marsiraji Thahir. This novel is examined by a psychological approach in literature, a literary approach that emphasizes the psychological aspects of the types and laws of psychology that can be applied to literary works. The data is qualitative since the purpose of this research is to explain or describe the psychological phenomena of the research deeply. The data were obtained by categorizing all the related dialogues and the narrations in the story, then psychologically analyzed. Triangulation was used to validate the data. After finishing all the steps of analyzing data, the interpretations were made based on the data and the theory. The results of the research were, psychologically, the main character in this novel is described as a person who often feels worried, frightened, keeping the reality up, and she is burdened by the problems faced. This portrayal is the representation of Wulan as a woman and woman emotionally and mentally is depicted as weakness person without having the ability to solve the problems.